Imaging lightning intracloud initial stepped leaders by low‐frequency interferometric lightning mapping array - Fanchao Lyu; Steven A. Cummer; Gaopeng Lu; Xuan Zhou; Joel Weinert (Geophysical Research Letters)
Abstract By comparing the source position of pulses during initial leaders and the paths of subsequent dart leaders from typical bilevel intracloud (IC) flashes, we demonstrate a new method to image the detailed three‐dimensional (3‐D) structure and stepping dynamics of IC initial leaders. Using this approach, we show that nearly half of the initial breakdown pulses are not involved in the main channel extension but instead originate in nonpropagating branches. The primary upward but significantly tilted initial leader channels propagated with measured mean/median 3‐D step length of 295/265 m and mean/median step interval of 1.05/0.6 ms. The structure and dynamics of IC initial upward negative leaders are distinct from those of highly branched cloud‐to‐ground downward negative leaders. We suggest that the tilted initial leader channel and electric field could affect the observation on leader‐associated high‐energy radiation phenomena, such as the position‐dependent observation of terrestrial gamma ray flashes from space‐based detectors.